Management of children exposed to Mycobacterium tuberculosis: a public health evaluation in West Java, Indonesia - Merrin E Rutherford; Rovina Ruslami; Melissa Anselmo; Bachti Alisjahbana; Neti Yulianti; Hedy Sampurno; Reinout van Crevel; Philip C Hill (Bulletin of the World Health Organization, 2013)
Objective To investigate qualitatively and quantitatively the performance of a programme for managing the child contacts of adult tuberculosis patients in Indonesia. Methods A public health evaluation framework was used to assess gaps in a child contact management programme at a lung clinic. Targets for programme performance indicators were derived from established programme indicator targets, the scientific literature and expert opinion. Compliance with tuberculosis screening, the initiation of isoniazid preventive therapy in children younger than 5 years, the accuracy of tuberculosis diagnosis and adherence to preventive therapy were assessed in 755 child contacts in two cohorts. In addition, 22 primary caregivers and 34 clinic staff were interviewed to evaluate knowledge and acceptance of child contact management. The cost to caregivers was recorded. Gaps between observed and target indicator values were quantified. Findings The gaps between observed and target performance indicators were: 82% for screening compliance; 64 to 100% for diagnostic accuracy, 50% for the initiation of preventive therapy, 54% for adherence to therapy and 50% for costs. Many staff did not have adequate knowledge of, or an appropriate attitude towards, child contact management, especially regarding isoniazid preventive therapy. Caregivers had good knowledge of screening but not of preventive therapy and had difficulty travelling to the clinic and paying costs. Conclusion The study identified widespread gaps in the performance of a child contact management system in Indonesia, all of which appear amenable to intervention. The public health evaluation framework used could be applied in other settings where child contact management is failing.